2015
DOI: 10.1111/irv.12323
|View full text |Cite
|
Sign up to set email alerts
|

Virological characterization of influenza H1N1pdm09 in Vietnam, 2010‐2013

Abstract: ObjectivesInfluenza A/H1N1pdm09 virus was first detected in Vietnam on May 31, 2009, and continues to circulate in Vietnam as a seasonal influenza virus. This study has monitored genotypic and phenotypic changes in this group of viruses during 2010–2013 period.Design and settingWe sequenced hemagglutinin (HA) and neuraminidase (NA) genes from representative influenza A/H1N1pdm09 and compared with vaccine strain A/California/07/09 and other contemporary isolates from neighboring countries. Hemagglutination inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Among the determined influenza type and subtype viruses, influenza A H1pdm09 was the major virus associated with hospitalization for SARI (221 313; 70.6 of all influenza cases). This finding is supported by NISS data from the study period, in which influenza A H1pdm09 was presented and predominated in 2011, 2013, and 2014, while A H3 occurred in 2012 and early 2014 (14). In our study, A H3 was detected in 11.6 of cases.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Among the determined influenza type and subtype viruses, influenza A H1pdm09 was the major virus associated with hospitalization for SARI (221 313; 70.6 of all influenza cases). This finding is supported by NISS data from the study period, in which influenza A H1pdm09 was presented and predominated in 2011, 2013, and 2014, while A H3 occurred in 2012 and early 2014 (14). In our study, A H3 was detected in 11.6 of cases.…”
Section: Discussionsupporting
confidence: 90%
“…1), while ILI incidence peaked twice per year in 2009-2013 period (14). An overlap in high SARI occurrence and high ILI occurrence in February and March was observed, indicating that increased ILI activity did not cause SARI hospitalization (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…After the pandemic in 2009/2010, A(H1N1)pdm09 became a fluctuant epidemic: A(H1N1)pdm09 prevailed for two years and then receded from dominance for a year. The results were consistent with those obtained by other researchers . The reason for the recurrent epidemics of A(H1N1)pdm09 was that the gradual accumulation of genetic changes and altered antigenicity enabled the viruses to evade host immune responses …”
Section: Discussionsupporting
confidence: 92%
“…During the seven flu seasons since its emergence, the A(H1N1)pdm09 virus underwent substantial genetic and antigenic changes that divided it into eight genetic groups and several subgroups . Phylogenetic analyses of the A(H1N1)pdm09 virus HA and NA genes isolated from Yantai during the study period indicated that the viruses mostly clustered in chronological order on the phylogenetic trees and that most Yantai strains were grouped into genetic clades 1.7, 6C, 6B.1 and 6B.2, which were similar to those circulating worldwide …”
Section: Discussionmentioning
confidence: 87%